Autologous transplantation of photoactivated subcutaneous adipose tissue improves glucose homeostasis in high‐fat diet‐induced obese mice. (18th July 2019) - Li, Rong; Li, Kai; Zhang, Liping; Wang, Lin; Chen, Ni; Deng, Xin; Luo, Mao; Wu, Jianbo
Abstract: Increasing evidence indicates that normal adipose tissue transplantation improves whole‐body energy metabolism and glucose homeostasis in a high‐fat diet (HFD)‐induced obese mouse model. Adipose tissue macrophages are associated with glucose homeostasis and insulin resistance in type 2 diabetes and obesity in humans, offering a potential target for therapeutics. However, whether transplantation of autologous adipose tissue that changes the macrophage phenotype directly contributes to systemic glucose intolerance has not been determined. We specifically developed our device, with more refined wavelengths of light to activate the macrophage phenotype in isolated subcutaneous white adipose tissue (sWAT) from host HFD mice. Autologous transplantation of photoactivated sWAT into HFD mice significantly reverses the M1 macrophage phenotype into M2, reduces the infiltration of macrophages in adipose tissues of HFD mice, and decreases the levels of proinflammatory cytokines. Strikingly, this transplantation reduced blood glucose levels and caused significant improvement in glucose tolerance, which was not shown in sham‐operated or nonphotoactivated sWAT‐transplanted HFD mice. Moreover, positron emission/computed tomography scans indicated higher glucose uptake in the heart but not in the liver, hindlimb muscles, or abdominal sWAT. These data suggested that the ability of photoactivation to shift Adipose tissue macrophage polarization in HFD mice caused a significant improvement in glucose homeostasis and that autologous transplantation might be a promising therapeutic option for the treatment of diabetes.